Mapping the morphology of complex words: A scientometric and pedagogical perspective - Danang Satria Nugraha; Suhailee Sohnui (JEELS (Journal of English Education and Linguistics Studies), 2026)
Complex word formation, a central process in morphology, has recently garnered increasing attention in linguistic research within the last decade. This study employs a scientometric approach to map the current landscape of this domain, aiming to reveal the field’s structure, trends, and thematic foci, with a focus on extracting pedagogical implications. Using VOSviewer software, we analyzed 488 documents retrieved from the Scopus database, spanning the years 2014 to 2024. The analysis revealed a dynamic field with an overall upward trend in publications, with a mean annual publication frequency of 48 documents across the 11-year period. A steady increase was observed from 2016 onwards, culminating in a peak in 2020. This peak signifies a growth of approximately 132% from the nadir of 2015. Leading researchers included Booij, G. and Plag, I., while Mental Lexicon and Morphology emerged as the most prominent publishers. Specifically, keyword analysis identified six distinct clusters: (1) fundamental concepts (25.5%); (2) language processing and acquisition (23.4%); (3) cognitive mechanisms (21.3%); (4) experimental perspectives (14.9%); (5) language development (9.6%); and (6) theoretical linguistics (5.3%). To some extent, these findings provide insights into the current state and future directions of complex word formation research, with implications for both linguistic theory and pedagogical practice.